Journal of the Malaysian Branch of the Royal Asiatic Society (JSTOR)
The Journal of the Malaysian Branch of the Royal Asiatic Society (JMBRAS) and its predecessors (The Journal of the Straits Branch of the Royal Asiatic Society, and the Journal of the Malayan Branch of the Royal Asiatic Society) have maintained continuous publication since 1878 except for the years of the Second World War. Originally produced by colonial administrators for an almost entirely expatriate readership, JMBRAS has evolved into the leading peer-reviewed academic journal dealing with history, culture and society in Malaysia, Singapore and Brunei.
Keywords: Asian Studies